THE CHANGE OF BANKING CULTURE: FACTORS AFFECTING ONLINE BANKING USAGE IN INDONESIA - Farida Komalasari; Fitriah Ramadhani (SAMPURASUN, 2020)
This research is aiming to find the factors of Indonesian online banking usage using Technology Acceptance Model (TAM). This was a quantitative research, analyzing primary data which are collected using online questionnaire. Total respondents were 202, chosen by purposive and snowball sampling method. Several criterias are used to test the data’s validity and reliability. Hypothesis testing is done by using structural equation model, starting from perceived ease of use as independent variable, followed by perceived usefulness, attitude towards use and behavioral intention to use as mediating variables, and actual system usage as dependent variable. The result shows perceived ease of use significantly influences perceived usefulness and attitude towards use. Perceived usefulness significantly influences attitude towards use, but does not significantly influence behavioral intention to use. Attitude towards use significantly influences behavioral intention to use. Lastly, behavioral intention to use significantly influences actual system usage. So, it can be concluded that the TAM can be used to analyze the Indonesian online banking usage. This research is the first research, applying an original TAM on Indonesian online banking usage using SEM.